2006
DOI: 10.1016/j.euje.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Parachute tricuspid valve

Abstract: Parachute abnormality of mitral valve frequently occurs with left sided obstructive lesions though occasionally may occur as an isolated lesion. Symptoms depend upon the severity of stenosis and associated lesions. Parachute abnormality of the tricuspid valve has rarely been reported and its association with left to right shunts has not been described so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Parachute tricuspid valve (PTV) was first described in a patient with Fallot's tetralogy . First echocardiographic demonstration of PTV was reported in a patient with atrial septal defect and ventricular septal defect, and showed a single papillary muscle on the septum similar to our case . Purvis et al .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Parachute tricuspid valve (PTV) was first described in a patient with Fallot's tetralogy . First echocardiographic demonstration of PTV was reported in a patient with atrial septal defect and ventricular septal defect, and showed a single papillary muscle on the septum similar to our case . Purvis et al .…”
supporting
confidence: 83%
“…3 First echocardiographic demonstration of PTV was reported in a patient with atrial septal defect and ventricular septal defect, and showed a single papillary muscle on the septum similar to our case. 4 Purvis et al 5 presented a young asymptomatic patient with parachute-like tricuspid valve. This is a congenital anomaly where two papillary muscles are present, but one is The PTV should have been kept in mind in patients with congenital heart defects because it is accompanied with congenital heart diseases.…”
mentioning
confidence: 99%
“…Shortly after its description involving the mitral tensor apparatus, it was observed that often, the anomaly was associated with left-sided obstructive lesions and the syndrome was called the Shone complex. 4 Parachute tricuspid valve is a late discovery 5 with a single case each reported with tetralogy of Fallot, 6 double-outlet right ventricle, 7 two cases with atrial septal defect 8,9 and three in isolation. [10][11][12] Most of these cases were not symptomatic due to parachute tricuspid valve.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a single case with associated atrial septal defect and parachute tricuspid valve has been reported. 4 Sometimes, the normal number of papillary muscles is seen, but one muscle is much larger than its peers and shows some characteristic features. This is known as a parachute-like asymmetric valve.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The first clinical description of the anomaly without right-sided obstructive lesions was made in 2006. 4 …”
Section: Introductionmentioning
confidence: 99%